Implementasi Dynamic Rendering untuk Optimasi Efisiensi Server dan Indeksabilitas Pada Single Page Application - Niko Achmad; Moh Ahsan; Ainia Walidaroyani (METHOMIKA: Jurnal Manajemen Informatika & Komputerisasi Akuntansi, 2026)
The development of a Client Side Rendering (CSR)-based Single Page Application (SPA) has search engine indexability weaknesses, while Server Side Rendering (SSR) overloads server computation. This study aims to prove the efficiency of the Dynamic Rendering architecture as a middle-ground solution. Through Nginx configuration, the server detects the User-Agent to serve static pages (CSR) to human users and fully rendered pages (SSR) to bot crawlers. Experimental testing was conducted on a Virtual Private Server (VPS) using k6 with a constant load of 100 Virtual Users, Prometheus, and Grafana, as well as Document Object Model (DOM) validation via Google Search Console. The Mann-Whitney U Test results proved a significant performance difference with a p-value < 0.05. The implementation of Dynamic Rendering is highly efficient, capable of reducing CPU Utilization by 92.28% and Memory Usage by 5.14%, and increasing Request Per Second (RPS) capacity by 17.19%. Indexability validation also confirmed that crawlers successfully received the HTML document entirely. In conclusion, Dynamic Rendering is proven to be an effective architectural solution to minimize server load while ensuring optimal content visibility on search engines.